2018
DOI: 10.1137/17m1158203
|View full text |Cite
|
Sign up to set email alerts
|

Faster Space-Efficient Algorithms for Subset Sum, $k$-Sum, and Related Problems

Abstract: We present randomized algorithms that solve Subset Sum and Knapsack instances with n items in O * (2 0.86n ) time, where the O * (·) notation suppresses factors polynomial in the input size, and polynomial space, assuming random read-only access to exponentially many random bits. These results can be extended to solve Binary Linear Programming on n variables with few constraints in a similar running time. We also show that for any constant k ≥ 2, random instances of k-Sum can be solved using O(n k−0.5 polylog(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 32 publications
(66 reference statements)
0
20
0
Order By: Relevance
“…More recently, these conjectures have become even more prominent as core problems in fine-grained complexity since their interesting consequences have expanded beyond geometry into purely combinatorial problems [102,113,38,72,12,6,83,7,62,72]. Note that k-SUM inherits its hardness from Subset Sum, by a simple reduction: to answer Open Question 1 positively it is enough to solve k-SUM in T 1−ε · n o(k) or n k/2−ε · T o(1) time.Entire books [91,79] are dedicated to the algorithmic approaches that have been used to attack Subset Sum throughout many decades, and, quite astonishingly, major algorithmic advances are still being discovered in our days, e.g., [88,68,26,51,14,108,77,61,44,15,16,85,56,22,94,82,33], not to mention the recent developments on generalized versions (see [24]) and other computational models (see [107,41]). At STOC'17 an algorithm was presented that beats the trivial 2 n bound while using polynomial space, under certain assumptions on access to random bits [22].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, these conjectures have become even more prominent as core problems in fine-grained complexity since their interesting consequences have expanded beyond geometry into purely combinatorial problems [102,113,38,72,12,6,83,7,62,72]. Note that k-SUM inherits its hardness from Subset Sum, by a simple reduction: to answer Open Question 1 positively it is enough to solve k-SUM in T 1−ε · n o(k) or n k/2−ε · T o(1) time.Entire books [91,79] are dedicated to the algorithmic approaches that have been used to attack Subset Sum throughout many decades, and, quite astonishingly, major algorithmic advances are still being discovered in our days, e.g., [88,68,26,51,14,108,77,61,44,15,16,85,56,22,94,82,33], not to mention the recent developments on generalized versions (see [24]) and other computational models (see [107,41]). At STOC'17 an algorithm was presented that beats the trivial 2 n bound while using polynomial space, under certain assumptions on access to random bits [22].…”
mentioning
confidence: 99%
“…Note that k-SUM inherits its hardness from Subset Sum, by a simple reduction: to answer Open Question 1 positively it is enough to solve k-SUM in T 1−ε · n o(k) or n k/2−ε · T o(1) time.Entire books [91,79] are dedicated to the algorithmic approaches that have been used to attack Subset Sum throughout many decades, and, quite astonishingly, major algorithmic advances are still being discovered in our days, e.g., [88,68,26,51,14,108,77,61,44,15,16,85,56,22,94,82,33], not to mention the recent developments on generalized versions (see [24]) and other computational models (see [107,41]). At STOC'17 an algorithm was presented that beats the trivial 2 n bound while using polynomial space, under certain assumptions on access to random bits [22]. At SODA'17 we have seen the first improvements (beyond log factors [100]) over the O(T n) algorithm, reducing the bound toÕ(T + n) [82,33].…”
mentioning
confidence: 99%
“…The BCM algorithm for E D does not straightforwardly extend to L D , and it is still open whether L D can be solved in n o(1) -space and n 2−Ω(1) time, even allowing random oracles. Recently, Bansal, Garg, Nederlof, and Vyas [BGNV18] showed that a variant of the BCM algorithm can be applied to solve L D with an improved running time, provided that the input arrays have small second frequency moment (i.e., there are few collision pairs within each arrays). Formally, define…”
Section: Dmentioning
confidence: 99%
“…Due to complicated dependencies on the paths in this random digraph, it looks difficult to reduce the number of random bits using pseudorandomness. It was asked as an open question [BCM13,BGNV18] whether the BCM algorithm can be modified to work with only "one-way access" to random bits, where we may toss up to O(t) coins in time t, but cannot randomly access arbitrary coins tossed in the past. In particular, [BCM13] stated it "seems plausible" that the random oracle in the BCM algorithm could be replaced by some family of poly log(n)-wise independent hash functions in the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Several classic algorithms for SubsetSum are typically taught in undergraduate courses, including the meet-in-the-middle algorithm running in time O(2 n/2 ) [25] and Bellman's dynamic programming algorithm running in pseudopolynomial time O(n • t) [12]. Surprisingly, after decades of research, major algorithmic advances were still discovered in the last 10 years, e.g., [39,33,21,7,24,8,9,32,11,38,14,31,27,1,10]. Among these developments, the most relevant for this paper are improvements over Bellman's O(n•t) algorithm: Koiliaris and Xu [31] designed a deterministic algorithm running in time 1 O(min{ √ n•t, t 4/3 }), and Bringmann [14] devised a randomized algorithm running in time O(t) (which was improved in terms of log factors in [27]).…”
Section: Subset Summentioning
confidence: 99%